Difa-e-Pakistan kay Darakhshanda Sitare - Noor Ahmad Khan, Major (Rawalpindi Department of History, GHQ, 2010)
Pak-o-Hind Jangon mein dad-e-shuja'at hasil krnay walay shohda, ghaziyon k ahwal.
Include Map and Illustrations.
It is the compilation of biographies. It is also edited by Major Noor Ahmad Khan.
Keywords: Military History - Pakistan -- Military History - Pak-Indo War -- Pak-Indo War -- Military History -- Pakistan -- Military History